Strategic Analyses taking into account Geopolitics and Geostrategic Issues - Matyjas, Zbigniew (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The main goal of the article is to answer the question whether and how to extend classic strategic analyzes to include geopolitics and geostrategy issues. Both of these terms are of particular importance when building possible strategic analyzes for major strategic projects in Poland. This applies, for example, to projects such as the Solidarity Transport Hub Poland, the construction of a nuclear power plant, or the development of transport connections. Also, issues related to national defense, both in the “hard” (army, military equipment) and “soft” aspects (e.g. cyber defense, development of Polish microelectronics), are largely linked to issues of geopolitics and geostrategy. Meanwhile, in the conditions of the domestic literature on the subject, these issues have not been the subject of serious scientific interest, hence a clear research gap in this respect can be observed. Therefore the task of the is to, at least partially, reduce this gap.